SCIENCE ON TRIAL: INDONESIA’S LEGAL DILEMMA - Fransiscus Nanga Roka,; Yovita Arie Mangesti, (Nusantara Hasana Journal, 2025)
This research analyzed the way in which Indonesia’s anti corruption court combines judicial formalism with scientific proof requirements. Employing a normative and comparative research design, we utilized a doctrinal analysis of Criminal Procedure Code and Anti Corruption Law, micro comparisons to the United States, UK, Singapore, and Indonesia including reliability tests; gatekeeping authority; chain of custody; expert independence. It found systemic epistemic deficits: the lack of an autonomous category for scientific evidence, weak to non existent reliability tests, fragmented chain of custody trade practices, judicial aversion to method and error rate scrutiny and an epistemic imbalance privileging prosecution access to experts and raw materials. Comparative mapping produced a hybrid gatekeeping model which integrates ex ante admission screening and ex post weight attribution, firmly based on validity of method, known error rates, transparent methodology, expert accreditation by the courts, court designated expertise appointment and data disclosure sanctions. We can only trust that rule making of the reliability standard, judicial gatekeeping and ensuring defendants’ rights are necessary in order to ensure due process and legal certainty. These structural changes bring evidentiary practice into closer conformity with scientific rationality, thereby mitigating the risks posed by wrongful convictions and enhancing public confidence in corruption adjudication